К вопросу о словообразовательном потенциале русского глагола - Бразаускене, Е. (Kalbotyra, 1981)
This article deals with the problem of studying the system of word-formation from the productive word and the analysis of microsystems of derivatives from different parts of speech.In consequence of the analysis of one formal-semantic group of the Russian derivative verbs (inchoative verbs with prefix ЗА-), we determine their derivational potentials, the factor influencing them and derivational semantic relations between derivative and productive words.